2022
DOI: 10.25105/mraai.v22i1.12627
|View full text |Cite
|
Sign up to set email alerts
|

Efektivitas Penggunaan E-Bupot 23/26

Abstract: This study aims to analyze the influence of the variables of quality system and user satisfaction on the effectiveness of use e-Bupot 23/26 with taxation understanding as a moderating variable by testing hypotheses that have been formulated previously. This type of research is descriptive with a quantitative approach. This study uses primary data with distributed questionnaire to corporate taxpayers who are registered with Tax Office of Central Jakarta and the sample were 69 respondents using convenience sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
1
4
0
1
Order By: Relevance
“…This research complimented several previous research results on the effectiveness and usefulness of technology-based features developed by DGT in improving taxpayer compliance (Cahyani et al, 2021;Karina et al, 2022;Subagiyo et al, 2023;Tita et al, 2022). Moreover, research also showed the existence of the Technology Acceptance Model (TAM) in the use of information technology, in this case E-Bupot.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This research complimented several previous research results on the effectiveness and usefulness of technology-based features developed by DGT in improving taxpayer compliance (Cahyani et al, 2021;Karina et al, 2022;Subagiyo et al, 2023;Tita et al, 2022). Moreover, research also showed the existence of the Technology Acceptance Model (TAM) in the use of information technology, in this case E-Bupot.…”
Section: Discussionsupporting
confidence: 87%
“…This convenience was certainly able to increase taxpayer compliance in making tax payments. In the context of taxpayers withholding/collecting taxes, the technological transformation used was in the form of E-Bupot (Lee, 2016;Iltizama, 2022;Karina et al, 2022). It provided convenience and data integration for taxpayers in withholding/ collecting taxes.…”
Section: Introductionmentioning
confidence: 99%
“…Namun, berdasarkan penelitian terdahulu ditemukan beberapa kendala yang dihadapi ketika menerapkan aplikasi e-Bupot PPh 23/26. Menurut Taha (2022) server e-Bupot PPh 23/26 masih seringkali down ataupun eror saat menginput data [3]. Penelitian serupa yang dilakukan oleh Karina & Simajuntak (2022) menyatakan bahwa aplikasi e-Bupot PPh 23/26 masih belum maksimal karena aplikasi masih seringkali eror saat mengimpor dan mengunggah data.…”
Section: Pendahuluanunclassified
“…However, please consider that the success of using a new system will depend on one's perception of the system. Karina & Simanjuntak (2022) research shows that taxpayers consider that the features available on e-Bupot 23/26 are still not optimal because they have yet to be able to provide convenience in fulfilling tax obligations, as indicated by the low results of user satisfaction for using the application. There is a change in making proof of withholding and submitting Periodic Income Tax Returns using the e-Bupot Unification application, which will raise perceptions of the use of the application.…”
Section: Pendahuluanmentioning
confidence: 99%
“…Based on these limitations, further research is expected to develop this research by expanding the scope of research, for example, by researching all KPPs in the DKI Jakarta area so that the research results can be more generalizable. Second, future research should add supporting variables such as combining the TAM model with Delone and Mclean's theory, namely system quality variables and user satisfaction as in research Karina and H Simanjuntak (2022) so that the research results can be used as a basis for determining service development strategies in the future.…”
mentioning
confidence: 99%